2019
DOI: 10.1111/jpy.12835
|View full text |Cite
|
Sign up to set email alerts
|

Parthenogenesis is rare in the reproduction of a sexual field population of the isogamous brown alga Scytosiphon (Scytosiphonaceae, Ectocarpales)

Abstract: Parthenogenetic development of unfused gametes is commonly observed in laboratory cultures among various brown algal taxa. There is, however, little information on the contribution of parthenogenesis to the reproduction of field populations. In this study, we investigated whether parthenogenesis is present in a sexual population of the isogamous brown alga Scytosiphon with a 1:1 sex ratio. In culture, both female and male gametes showed higher mortality and slower development compared to zygotes. More than 90%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Histograms based on the haploid data set showed that pairs of individuals having genetic distances of less than 11 were rare in sexual populations (seven pairs out of a total of 7,021 pairs), but abundant in parthenogenetic populations (221 pairs out of a total of 4,278 pairs; Figure 4). A previous study showed that parthenogenesis rarely occurred in a sexual population of Scytosiphon shibazakiorum (as Scytosiphon species IIa; Hoshino & Kogame, 2019), a close relative of S . lomentaria .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Histograms based on the haploid data set showed that pairs of individuals having genetic distances of less than 11 were rare in sexual populations (seven pairs out of a total of 7,021 pairs), but abundant in parthenogenetic populations (221 pairs out of a total of 4,278 pairs; Figure 4). A previous study showed that parthenogenesis rarely occurred in a sexual population of Scytosiphon shibazakiorum (as Scytosiphon species IIa; Hoshino & Kogame, 2019), a close relative of S . lomentaria .…”
Section: Resultsmentioning
confidence: 99%
“…lomentaria is isogamous and both female and male gametes have parthenogenetic ability, male parthenogens were not found. This is probably due to the more inferior parthenogenetic ability of male gametes than that of females (Hoshino & Kogame, 2019; Hoshino et al, 2019). Females are likely to have more potential than males to evolve into parthenogens in this species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first scenario, a mutation leading to loss of pheromone production triggers the loss of sex (i.e., ‘spontaneous origin’, (Simon et al ., 2003). Because female gametes are capable of parthenogenesis, then the female-parthenogenetic population expands whereas males would decay because they cannot undergo efficient parthenogenesis (Hoshino & Kogame, 2019). In the second scenario, males are less tolerant to a change in environmental conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%